Republic of Congo : 2008 Article IV Consultation, Requests for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries, and Financing Assurances Review; Staff Report; Staff Statement and Supplement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Congo. (IMF Staff Country Reports; Country Report ;, 2009)
The staff report for the Republic of Congo's combined 2008 Article IV Consultation and Requests for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility is discussed. To enhance external viability, the authorities recognize the need to improve competitiveness, raise output growth through diversification, and consolidate the fiscal position. The authorities are making a concerted effort to improve the business climate, liberalize trade, deepen financial intermediation, continue reform of public enterprises, improve governance and transparency, and put in place development strategies in key sectors.